A bibliometric analysis of Mediterranean diet on cancer from 2012 to 2021 - Liu, Yafeng; Lu, Jibin (Frontiers in Nutrition, 2023)
Background: Numerous studies have demonstrated the value of the Mediterranean diet (MD) as a nutritious eating regimen for lowering the risk of cancer. However, the general trend in this area is unclear. From a bibliometrics standpoint, this study intends to discuss the research patterns, existing state, and possible hotspots in this area. Methods: The Web of Science Core Collection (WoSCC) was searched for articles on cancer that were related to MD. For bibliometric analysis and visualization, CiteSpace, VOSviewer, Microsoft Excel 2019, and R software were utilized. Results: There were 1415 articles and reviews from 2012 to 2021. Annual publication volume shows a continuous upward trend. Italy and Harvard University are the countries and institutions with the most publications. Nutrients ranks first in the number of documents, the number of citations, and the H-index. James R Hebert is the most productive writer, and Antonia Trichopoulou is the most co-cited author. “Alcohol consumption”, “Oleic acid”, and “Low density lipoprotein” were earlier keywords, while more recent hotspots focused on “gut microbiota”, “older adult”, and “ polyphenol ”. Conclusion: Over the past decade, research on MD in the field of cancer has received increasing attention. Research on MD and cancer has drawn more attention. To improve the level of evidence for the MD‘s beneficial effects on a range of cancers, more research on molecular mechanisms and better clinical studies are urgently required.